PROFESSIONAL CULTURE OF TEACHERS OF HIGHER EDUCATION IN THE CONDITIONS OF INFORMATION - Yorqinbek, Aslanov (Journal of Higher Education and Academic Advancement, 2024)
This is it in the article information conditions higher education of teachers professional culture development according to and information conditions of students information communication in technologies use degrees increase about word held.